2015
DOI: 10.1073/pnas.1517045112
|View full text |Cite
|
Sign up to set email alerts
|

PSD-95 family MAGUKs are essential for anchoring AMPA and NMDA receptor complexes at the postsynaptic density

Abstract: The postsynaptic density (PSD)-95 family of membrane-associated guanylate kinases (MAGUKs) are major scaffolding proteins at the PSD in glutamatergic excitatory synapses, where they maintain and modulate synaptic strength. How MAGUKs underlie synaptic strength at the molecular level is still not well understood. Here, we explore the structural and functional roles of MAGUKs at hippocampal excitatory synapses by simultaneous knocking down PSD-95, PSD-93, and synapse-associated protein (SAP)102 and combining ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
211
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 252 publications
(220 citation statements)
references
References 87 publications
8
211
0
1
Order By: Relevance
“…EM tomography suggested that the NMDAR nanodomains contained NMDAR-PSD95 complexes in 1:2 stoichiometry and that other PSD regions with AMPARs, but without NMDARs, contained extended PSD95-AMPAR complexes in a 1:1 stoichiometry (2). When PSD95 was acutely knocked down, AMPAR nanodomains were lost, whereas NMDAR nanodomains in PSDs were relatively preserved, consistent with the NMDAR nanodomains being more stable (1,41). The presence of separate AMPAR and NMDAR domains in PSDs provides a simple explanation for why PSD95 palmitoylation and depalmitoylation are different at AMPARs and NMDARs.…”
Section: Discussionmentioning
confidence: 81%
“…EM tomography suggested that the NMDAR nanodomains contained NMDAR-PSD95 complexes in 1:2 stoichiometry and that other PSD regions with AMPARs, but without NMDARs, contained extended PSD95-AMPAR complexes in a 1:1 stoichiometry (2). When PSD95 was acutely knocked down, AMPAR nanodomains were lost, whereas NMDAR nanodomains in PSDs were relatively preserved, consistent with the NMDAR nanodomains being more stable (1,41). The presence of separate AMPAR and NMDAR domains in PSDs provides a simple explanation for why PSD95 palmitoylation and depalmitoylation are different at AMPARs and NMDARs.…”
Section: Discussionmentioning
confidence: 81%
“…For n channels, the probability of at least one receptor opening is the same as the complement of the probability that all receptors fail to open (1− P o ) n , or P event = 1−(1− P o ) n . Although we do not know how many NMDARs are present on each MSN spine, studies from CA1 pyramidal neurons suggest between 1 and 10 functional NMDARs at the synapse (Chen et al, 2015; Nimchinsky et al, 2004; Spruston et al, 1995). Thus the likelihood of observing an event, given a steady-state concentration of 25 nM glutamate, is estimated to be between 0.004 and 0.041 (for n = 1 or n = 10, respectively).…”
Section: Discussionmentioning
confidence: 90%
“…Extending these findings, we performed immuno-EM analysis from mouse primary neuronal cultures, as these preparations are largely devoid of non-neuronal cell types and can provide higher resolution analysis 20,21 . No immunogold label was observed in samples treated with secondary gold-conjugated antibodies alone (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%